2019
DOI: 10.1371/journal.pone.0210943
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic significance of DAPK promoter methylation in lymphoma: A meta-analysis

Abstract: We aimed to characterize the clinical significance of epigenetic loss of death-associated protein kinase (DAPK) gene function through promoter methylation in the development and prognosis of lymphoma. PubMed, Web of Science and ProQuest databases were searched for relevant studies. Twelve studies involving 709 patients with lymphoma were identified. The prognostic value of DAPK methylation was expressed as risk ratio (RR) and its corresponding 95% confidence interval (CI), while the associations between DAPK m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In hematological cancers such as monoclonal gammopathies, it was observed that DAPK methylation might be a marker of disease progression with a negative impact on disease prognosis [39]. A more recent study in lymphoma patients also demonstrated that DAPK promoter methylation might serve as a negative prognostic biomarker even though it is not associated with lymphoma progression [40]. Despite the impact of DNA methylation in several neoplasias, it is important to point out that there is also a link between DNA methylation and aging, showing the establishment of global hypomethylation and regions of CpG-island methylation with age [41].…”
Section: Discussionmentioning
confidence: 99%
“…In hematological cancers such as monoclonal gammopathies, it was observed that DAPK methylation might be a marker of disease progression with a negative impact on disease prognosis [39]. A more recent study in lymphoma patients also demonstrated that DAPK promoter methylation might serve as a negative prognostic biomarker even though it is not associated with lymphoma progression [40]. Despite the impact of DNA methylation in several neoplasias, it is important to point out that there is also a link between DNA methylation and aging, showing the establishment of global hypomethylation and regions of CpG-island methylation with age [41].…”
Section: Discussionmentioning
confidence: 99%
“…DAPK1 plays a role in lymphomas, as recently demonstrated by a meta-analysis where hypermethylation of the promoter was found to be associated with the 5-year survival rate of patients ( 8 , 9 ). Overall, DAPK1 hypermethylation corresponds to a significantly lower survival and represents an independent, negative prognostic biomarker ( 8 ).…”
Section: Introductionmentioning
confidence: 73%
“…Hypermethylated KLF4 has also been associated with the poor prognosis of patients with splenic marginal zone lymphomas (SMZL) and SMZL cell lines exposed to hypomethylating agents show a reduced proliferation (6,7). DAPK1 plays a role in lymphomas, as recently demonstrated by a meta-analysis where hypermethylation of the promoter was found to be associated with the 5-year survival rate of patients (8,9). Overall, DAPK1 hypermethylation corresponds to a significantly lower survival and represents an independent, negative prognostic biomarker (8).…”
Section: Klf4 Dapk1 and Spg20 Promoter Methylation Is Not Affected By Dnmt1 Silencing And Hypomethylating Drugs In Lymphoma Cellsmentioning
confidence: 90%
See 1 more Smart Citation
“…In light of these issues, PLOS ONE cannot stand by the reliability of the reported research, and the PLOS ONE Editors retract this article [ 1 ].…”
mentioning
confidence: 99%